FAKTOR PENYEBAB MEDICATION ERROR DI INSTALASI GAWAT DARURAT (IGD) RUMAH SAKIT BHAYANGKARA TK.III MANADO - Angkow, Leydia; Citraningtyas, Gayatri; Wiyono, Weny I. (UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTPatients who enter the ECU room need fast and appropriate help, but in reality there are reports of Medication Errors in the ECU. The purpose of this research is to find out the causes factors of Medication Error in the prescribing and dispensing phase. This research is a descriptive study with prospective data collection using questionnaires. The results showed that the factors causing Medication Error on prescribing phase error included the workloads that were unbalanced of workloads and human resources (HR), interruptions which were interrupted by ringing the telephone, communication such as the incomplete writing of drug names, environmental conditions such as the temperature working area was less supportive while working, and education, namely prescription writing that does not meet the prescription completeness requirements. Factors that causes Medication Error on dispensing phase include workloads of health workers are not able to solve on the every of their own job, interruptions that interrupting working by telephone ringing, environmental conditions on the work area temperature is less supportive when working, education such as preparation of drugs that are not in recipe request, and communication, namely the communication system regarding the stock of pharmaceutical supplies in the Pharmacy Installation did not run smoothly.Keywords: Causes, Medication Error, Emergency Room, Bhayangkara Hospital.ABSTRAKPasien yang masuk IGD perlu pertolongan yang cepat dan tepat, namun kenyataannya terdapat pelaporan kejadian Medication Error di IGD. Tujuan penelitian yaitu mengetahui faktor penyebab Medication Error pada fase prescribing dan dispensing. Penelitian ini merupakan penelitian deskriptif dengan pengambilan data secara prospektif menggunakan kuisioner. Hasil penelitian menunjukkan bahwa faktor penyebab Medication Error fase prescribing meliputi beban kerja yaitu beban kerja dan SDM tidak seimbang, gangguan/interupsi bekerja yaitu terganggu dengan dering telepon, komunikasi yaitu penulisan nama obat tidak lengkap, kondisi lingkungan yaitu suhu area kerja kurang mendukung saat bekerja, dan edukasi yaitu penulisan resep yang tidak memenuhi syarat kelengkapan resep. Faktor penyebab Medication Error fase dispensing meliputi beban kerja yaitu tenaga kesehatan tidak mampu menyelesaikan sendiri setiap pekerjaan, gangguan/interupsi bekerja yaitu terganggu dengan dering telepon, kondisi lingkungan yaitu suhu area kerja kurang mendukung saat bekerja, edukasi yaitu penyiapan obat yang tidak sesuai permintaan resep dan komunikasi yaitu sistem komunikasi mengenai stok perbekalan farmasi di Instalasi Farmasi tidak berjalan lancar.Â Kata Kunci: Faktor penyebab, Medication Error, Instalasi Gawat Darurat, Rumah Sakit Bhayangkara